Proprioception and dynamic balance performance in wrestlers: Freestyle vs. Greco-Roman - Tabasi, S. R.; Norasteh, A. A.; Mirzaei, B.; Zarei, H. (Science & Sports, 2022)
Objectives The aim of this study was to compare proprioception and dynamic balancebetween freestyle and Greco-Roman wrestlers. Equipment and methods In this study, 42 national level wrestlers (freestyle [FS], n = 21 and Greco-Roman [GR], n = 21) volunteered to participate and performed a battery of tests including: Y balance-test and upper quarter YBT to measure lower and upper-extremity balance performance, an electrogoniometer to measure proprioception and range of motion, and dynamometer to measure sense of force and muscles strength in wrestlers. Results No significant differences were observed in YBT (P = 0.37), ankle plantar flexor strength (P = 0.44), range of motion in ankle plantar flexion (P = 0.42) and shoulder flexion (P = 0.75) between the GR and FS wrestlers. There were significant differences in YBT-UQ (P = 0.001), shoulder flexor strength (P = 0.002), error sense of force in ankle plantar flexors (P = 0.001) and shoulder flexors (P = 0.037), error joint reposition in ankle plantar flexion (P = 0.001) and shoulder flexion (P = 0.001) between the GR and FS wrestlers. It seems that a difference in the nature of exercises and competitions in FS and GR wrestlers needed different adaptations in muscular and neuromuscular performance.